Analisis Efisiensi Hibah pada Dinas Pemberdayaan Masyarakat dan Kampung Provinsi Papua Barat - Endar E. Novriyanti; Paulus K. Allo Layuk; Arius Kambu (Universitas Cenderawasih, 2022)
Grants as one of the components of regional finances which are stated annually in the Regional Revenue and Expenditure Budget (APBD) should be managed in an orderly manner, obeying laws and regulations, efficient, economic, effective, transparent and responsible by paying attention to the principles of justice, propriety , rationality and benefits to society. In the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 32 of 2011 concerning Guidelines for Providing Grants and Social Assistance Sourced from Regional Revenue and Expenditure Budgets. The results of the research on the process of implementing grant spending are in accordance with Permendagri number 32 of 2011 which can be seen from the results of the questionnaires that have been distributed where the results of their statements state that the implementation of the grant spending budget is categorized as quite efficient. The level of efficiency of the grant spending budget in the community empowerment office and village of West Papua province in 2017-2020, overall is well managed. However, there are some obstacles encountered.